Correlation of Glomerular Size With Donor–Recipient Factors and With Response to Injury. Issue 11 (21st October 2021) - Grande, Joseph P.; Helgeson, Erika S.; Matas, Arthur J.
Abstract : Supplemental Digital Content is available in the text. Abstract : Background: Glomerular size in renal allografts is impacted by donor–recipient factors and response to injury. In serial biopsies of patients with well-functioning grafts, increased glomerular size correlates with better survival. However, no previous study has addressed the association of glomerular size at the time of a for-cause biopsy and clinical/histopathologic markers of injury, or effect on long-term graft outcome. Methods: Two cohorts of kidney transplant recipients enrolled in the Deterioration of Kidney Allograft Function study were evaluated. The prospective cohort (PC, n = 581): patients undergoing first for-cause kidney biopsy 1.7 ± 1.4 (mean ± SD) y posttransplant; and the cross-sectional cohort (CSC, n = 446): patients developing new-onset renal function deterioration 7.7 ± 5.6 y posttransplant. Glomerular planar surface area and diameter were measured on all glomeruli containing a vascular pole. Kidney biopsy was read centrally in a blinded fashion according to the Banff criteria. Results: Glomerular area was significantly higher in the CSC than the PC; time from transplant to indication biopsy was associated with glomerular area in both cohorts ( P values ≤ 0.001). Glomerular area was associated with indices of microvascular inflammation (glomerulitis, peritubular capillary infiltrates; P values ≤ 0.001) and segmental glomerulosclerosis ( P value < 0.0001). In the CSC, higher glomerular area was associated with higher estimated glomerular filtration rate ( P value ≤ 0.001) and increased graft survival after accounting for microvascular inflammation (adjusted hazard ratio = 0.967; 95% confidence interval: 0.948-0.986; hazard ratio in biopsies without evidence of diabetes or antibody mediated rejection = 0.919, 95% confidence interval: 0.856-0.987). Conclusions: Glomerular size is associated with histopathologic features present at the time of indication biopsy and with increased graft survival in the CSC.